2015
DOI: 10.1093/europace/euv204
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory cardiac arrhythmias in relation to mild hypokalaemia and prognosis in community dwelling middle-aged and elderly subjects

Abstract: In middle-aged and elderly subjects with no manifest heart disease, mild hypokalaemia is associated with increased rate of ventricular but not supraventricular arrhythmias. Hypokalaemia interacts synergistically with increased ventricular ectopy to increase the risk of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…Thus, event rates in subjects with ESVEA and accompanying hypokalemia were almost 14× greater compared with the event rates seen when no ESVEA or hypokalemia were present. According to this study and previous studies, hypokalemia seems to be independently associated with a worse prognostic outcome in terms of cardiovascular-related events, 6,[17][18][19] and data from the present study suggest that mild hypokalemia interacts with excessive supraventricular ectopy to increase the risk of stroke significantly. Earlier studies has shown ESVEA as a predictor of atrial fibrillation and stroke.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, event rates in subjects with ESVEA and accompanying hypokalemia were almost 14× greater compared with the event rates seen when no ESVEA or hypokalemia were present. According to this study and previous studies, hypokalemia seems to be independently associated with a worse prognostic outcome in terms of cardiovascular-related events, 6,[17][18][19] and data from the present study suggest that mild hypokalemia interacts with excessive supraventricular ectopy to increase the risk of stroke significantly. Earlier studies has shown ESVEA as a predictor of atrial fibrillation and stroke.…”
Section: Discussionsupporting
confidence: 83%
“…In a recent study, mild hypokalemia was found to be associated to increased risk of mortality in a hypertensive population, 24 and these data are consistent with our previous findings in the Copenhagen Holter Study cohort. 19 Even though our study population had hypertensive blood pressure values at baseline, adjustments for systolic blood pressure did not change significance in terms of end points in neither the previous nor the present study. Therefore, it seems likely that the effect of the possible RAAS activation exceeds an increased blood pressure level.…”
Section: Discussioncontrasting
confidence: 70%
“…The association between abnormal values of potassium and adverse outcomes may be explained by underlying disruption in kidney function, or by downstream effects of potassium itself. Both hypo- and hyperkalemia have been associated with arrhythmias, [39][40][41][42][43] which can cause sudden cardiac death. Potassium levels affect the resting membrane potential of cardiomyocytes and the activity of potassium channels important for the cardiac electrical cycle, with hypokalemia inducing hyperpolarization, faster electrical conduction, and delays in ventricular repolarization, and hyperkalemia resulting in slower electrical conduction.…”
Section: Discussionmentioning
confidence: 99%
“…Hypokalemia is a common electrolyte disorder and complication of hospitalized patients. Serum K + has been confirmed to be a predictor of adverse cardiovascular and renal outcomes [1215], but there has been only 1 previous report of hypokalemia being associated with high short-term mortality in acute stroke patients [16]. …”
Section: Introductionmentioning
confidence: 99%